Biological Markers and Response to Neoadjuvant Taxane-Based Chemotherapy in Patients with Locally Advanced Breast Cancer. (17th December 2012) - El-sayed, Mohamed I.; Maximous, Doaa W.; Zakhary, Madeha M.; Mikhail, Nabiel N. H.
Abstract : Introduction . Biological markers as Her2/neu, p53, and hormonal receptors (HmRs) may be reliable parameters for prognostic assessment of patients of locally advanced breast cancer (LABC). This work aims at assessing the potential value of these biological markers for the prediction of disease outcome after neoadjuvant taxane-based chemotherapy and its implication on the surgical role. Patients and Methods . From March 2006 to September 2011, 95 patients with LABC were treated by neoadjuvant taxane-based chemotherapy given at intervals of 3 weeks. Expression of Her2/neu and p53 was examined in the initial tissue biopsy by using ELISA technique. Status of HmRs was determined using a commercial enzyme immunoassay. Three weeks after the third cycle, patients underwent surgical resection followed by 3 more cycles of taxane-based chemotherapy and radiotherapy as an adjuvant therapy. Relations of Her2/neu overexpression to p53, HmRs, and conventional prognostic factors were analyzed. Results . Median followup was 61 months. The 5-year DFS and OAS rates were significantly higher in patients with positive HmRs than in those with negative HmRs, patients with Her2− than those with Her2+ breast cancer, and patients with intact p53 breast cancer than those with inactive p53. HER-2 overexpression was statistically significant associated with loss of HmR positive immunostaining (P < 0.0001 ), grade III breast cancer (P < 0.0001 ), advanced nodal status (P = 0.0039 ), and younger (<50 years) age (P = 0.0108 ). Conclusion . Her2/neu overexpression was associated with poor DFS and OAS rates, as it was significantly associated with negative HmR and high grade.